The governance of global land sector semantic resources - status and pathways - Stubkjaer, Erik; Whittal, Jennifer; Hull, Simon; Cagdas, Volkan; Bayer, Charl-Thom; Meggiolaro, Laura; Bennett, Rohan; Todorovski, Dimo; Kara, Abdullah; Folmer, Erwin (TAYLOR & FRANCIS LTD, 2025)
Knowledge Organization Systems (KOS) enable Semantic Web and Linked Data implementations. KOS in terms of the Linked Land Governance Thesaurus (LandVoc) and the Cadastre and Land Administration Thesaurus (CaLAThe) render concepts of the ISO 19152:2024 Land Administration Domain Model. These all support more shared and standardized understandings in the land domain. Concept mapping is presented, and an explicit integration of thesauri and knowledge bases is illustrated for education and community engagement. The paper reflects on the integration of CaLAThe into the LandVoc and AGROVOC context. The establishment of a less strict semantic facility, supporting ad hoc teaching tasks, is motivated.
Keywords: AGROVOC multilingual thesaurus (AGROVOC); Cadastre and Land Administration Thesaurus (CaLAThe); The Linked Land Governance Thesaurus (LandVoc); Teaching Essentials for Responsible Land Administration (TERLA); concept mapping; FRAMEWORK; Engineering; Geology; Remote Sensing